1999
DOI: 10.1038/sj.bmt.1702061
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced assessment of allogeneic bone marrow transplant engraftment using automated fluorescent-based typing

Abstract: Summary:Traditional qualitative gel electrophoresis approaches lack accurate and quantitative assessment of mixed chimerism in BMT patients. The likelihood of informative markers is greatly increased using simultaneous amplification of 10 highly polymorphic loci with fluorescent-labeled primers in an automated DNA sequencer. This allows for more precise interpretation of mixed chimerism with a detection level approximating 1%. To evaluate this approach to quantitative assessment of chimeric populations we mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
0
24
1
1
Order By: Relevance
“…In contrast to Pindolia et al, 19 we have found that the presence of stutter peaks causes serious problems with both the interpretation and quantitation of chimerism. As discussed earlier, our selection criteria exclude the use of markers where donor and recipient alleles are separated by just one repeat unit.…”
Section: Troubleshootingcontrasting
confidence: 48%
“…In contrast to Pindolia et al, 19 we have found that the presence of stutter peaks causes serious problems with both the interpretation and quantitation of chimerism. As discussed earlier, our selection criteria exclude the use of markers where donor and recipient alleles are separated by just one repeat unit.…”
Section: Troubleshootingcontrasting
confidence: 48%
“…Several methods for evaluating chimerism have been developed, including cytogenetic and molecular techniques. The most widely used technique for evaluating chimerism is polymerase chain reaction (PCR) amplification of short tandem repeats (STR) [4][5][6][7][8][9][10]. However, the sensitivity of this method is only approximately 1-5%, even when fluorescent-labeled primers and an automated DNA sequencer are used [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical follow up of the allograft recipients requires long-term monitoring of either the malignancyspecific markers or the residual hematopoiesis of the recipient cells (mixed chimerism, MC). Minimal residual disease (MRD [1,2]) monitoring involves detection and quantification of the malignancyspecific markers, while measuring the extent of mixed chimerism [3] requires measuring the fraction of recipient cells in peripheral blood samples. MRD approaches require monitoring the malignant clone via molecular (PCR-based) or immunophenotypic methods [4].…”
Section: Introductionmentioning
confidence: 99%